PENINGKATAN KUALITAS PENGAJAR KEAGAMAAN DENGAN PROGRAM GURU PENGABDIAN MASYARAKAT DI DESA KALIKIDANG SOKARAJA BANYUMAS - Harisman, Harisman; Maftuchah, Farichatul; Alfais, Ahmad Khanif Sofyan; Sulamiah, Esti Barokah (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Improving the quality of religious teachers is an important effort to strengthen religious education in society. The Community Service Teacher Program (GPM) in Kalikidang Village, Sokaraja, Banyumas, is an initiative that aims to increase the competency and involvement of religious teachers in social services and religious education. This research aims to evaluate the effectiveness of the GPM program in improving the quality of religious teachers in Kalikidang Village. The research method uses a qualitative approach with data collection techniques through interviews, observation and document analysis. The research results show that the GPM program has succeeded in improving the quality of religious teachers through training, mentoring and providing certification. Teachers demonstrated improvements in religious understanding, teaching skills, and service to the community. Apart from that, the GPM program has also succeeded in increasing community participation in religious activities and social services. Thus, the GPM program in Kalikidang Village makes a positive contribution in strengthening religious education and improving the quality of religious life at the local level. The implication of this research is the importance of continuing and developing similar programs in improving the quality of religious education in rural communities.